Response of Eucalyptus Clones to Different Mrigation Regimes in Plantation - Srivastava, Varun; Singh, Avtar; Vashist, K. K. (Indian Forester, 2011)
The leaf N. P. K and chlorophyll content in four different clone numbers viz. 72. 413. 2045 and 2070 of Eucalypts as influenced by three different irrigation regimes was studied in field conditions. The sampling of leaves was carried out during June and December 2007. The results of the study revealed that the accumulation of leaf N was higher in 50mm CPE in clone number 413 during June and December 2007. However, leaf P and K concentrations were significantly increased in clone number 413 when irrigation was 50mm and 75mm CPE during December 2007. Where as, the chlorophyll content was higher in clone number 413. In irrigation regime CPE at 50mm all the clones differed significantly with respect to chlorophyll content when irrigation frequency reduced to 100mm CPE chlorophyll content reduced, significantly in aU the clones during June and December 2007. Under aU the irrigation regimes the clone 2045 proved to be inferior to all other clones under study with regards to chlorophyll content where as, clone 413 maintained its superiority over other clone under study.